Estudo das relações entre bullying e esquemas iniciais desadaptativos em estudantes universitários - Borges, Vanessa Lima (2017)
This study aimed to deepen the knowledge about the bullying phenomenon and the effects caused on the individuals from the point of view from the Early Maladaptive Schemas (EMS) described by Jeffrey E. Young in a non-clinical sample. A total of 236 students from 5 higher education groups from the Universidade Federal de Uberlândia (Federal University of Uberlandia), including Nutrition, Physical Education, Computing, Pedagogy, Psychology, from both genders, from age 18 to 54 answered to the Young Schema Questionnaire – Short Form, a Bullying Victimization Scale (EVB) and socioeconomic questionnaire to draw a profile sample. In order to establish the correlation between the data obtained with the measurement instruments, the Spearman Correlation Coefficient (ρ) was calculated. The results showed positive correlations between EMS and victimization through bullying on the different courses of the university studied. Therefore, there was no specific type of scheme for the victims of bullying, but a variety of them in different schematic areas, which emphasizes the need to consider the individual differences and particularities of each course. The Physical Education course was the one that presented the highest record of bullying following was the course of Psychology, Computing, Nutrition and Pedagogy. The most frequent type of victimization in both genders was verbal bullying, since relational bullying was more frequent between women and physical bullying among men. Based on the results of the research it is possible to verify that bullying is present in the academic environment and can cause consequences like the reinforcement or maintenance of the EMS. Otherwise the EMS provokes a fragility on the victims to find effective resources to overcome these aggressions. Based on these understandings, we believe that, the Therapy Focused on Schemes proposed by Young has great potential for interventions aimed at working with the trauma caused by bullying and the need to propose strategies to prevent this form of victimization in the academic environment.